Pênfigo foliáceo em eqüino: relato de caso - Oliveira Filho, José Paes de [UNESP]; Goncalves, Roberto Calderon [UNESP]; Chiacchio, Simone Biagio [UNESP]; Amorim, Rogerio Martins [UNESP]; Conceição, L. G.; Borges, Alexandre Secorun [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Diagnosticou-se pênfigo foliáceo em um eqüino macho, castrado, quatro anos de idade da raça Árabe apresentando dermatite generalizada caracterizada por placas escamo-crostosas e presença de dermatite pustular acantolítica subcorneal.

Pemphigus foliaceus was diagnosed in a four-year-old Arabian equine gelding, with generalized dermatitis characterized by scaling and crusting plaques and acantholytic subcorneal pustular dermatitis.
Equine pemphigus foliaceous: case report
Keywords: eqüino; pênfigo foliáceo; dermatite; equine; pemphigus foliaceus; dermatitis